2022
DOI: 10.18394/iid.999971
|View full text |Cite
|
Sign up to set email alerts
|

Öz-Şefkatin Görev Performansı Üzerindeki Etkisinde Psikolojik Sermayenin Aracılık Rolü

Abstract: Bu araştırmanın temel amacı, öz-şefkatin görev performansı üzerindeki etkisinde psikolojik sermayenin dolaylı bir etkiye (aracı etki) sahip olup olmadığını belirlemektir. Zaman ve maliyet kısıtları nedeniyle kolayda örnekleme yönteminin kullanıldığı araştırmada veriler, Tokat ili ve ilçelerindeki kamu hastanelerinde görev yapan 176 sağlık personelinden elde edilmiştir. Analiz sonuçlarına göre, öz-şefkat görev performansı (ϸ=.37, p<.001) ve psikolojik sermayeyi (ϸ=.49, p<.001) pozitif yönde etkilemiştir. Psikol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Additionally, research has shown that self-compassion positively impacts performance (Barnard & Curry, 2011;Killham et al, 2018;Egan et al, 2022). A study conducted by Polatcı & Baygın (2022) found that self-compassion had a positive impact on task performance and psychological capital and found that psychological capital plays an intermediary role. Künye & Aydıntan (2020) revealed that there is a positive relationship between self-compassion and intrinsic motivation, and intrinsic motivation and job satisfaction, self-compassion and job satisfaction.…”
Section: Relationship Between Self-compassion Extrinsic Motivation In...mentioning
confidence: 99%
“…Additionally, research has shown that self-compassion positively impacts performance (Barnard & Curry, 2011;Killham et al, 2018;Egan et al, 2022). A study conducted by Polatcı & Baygın (2022) found that self-compassion had a positive impact on task performance and psychological capital and found that psychological capital plays an intermediary role. Künye & Aydıntan (2020) revealed that there is a positive relationship between self-compassion and intrinsic motivation, and intrinsic motivation and job satisfaction, self-compassion and job satisfaction.…”
Section: Relationship Between Self-compassion Extrinsic Motivation In...mentioning
confidence: 99%
“…Tarama deseni, bireylerin belirli konularda tutum, görüş, beklenti ve özelliklerini anket aracılığıyla belirlemeyi amaçlayan araştırmalar şeklinde tanımlanmaktadır (Gürbüz ve Şahin, 2017). Psikolojik dayanıklılığın işgören performansı üzerindeki etkisinde öz-şefkatin aracı rol üstlenip üstlenmediğinin incelendiği araştırmada, araştırma modeli alanyazında yer alan ilgili çalışmalardan faydalanılarak oluşturulmuştur (Cooke vd., 2019;Kim ve Han, 2021;Kumarı ve Sangwan, 2015;Polatcı ve Baygın, 2022;Shebuski vd., 2020;Yelpaze, 2020).…”
Section: Araştırma Modeliunclassified
“…Personal development is necessary to increase resilience, which is a component of psychological capital. Therefore, in order to increase the quality of the outputs obtained in the organization and the performance of the individuals working in the organization, managers should contribute to the personal development of the employees and create opportunities for them at this point (Polatcı and Baygın, 2022). It can be said that the variables of self-compassion and psychological resilience are important in increasing employee performance within the framework of those mentioned in the literature.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
See 2 more Smart Citations